The Effect of Lipopolysaccharide Challenge in RAW 264.7 Cells on Nitric Oxide Release and Cell Viability - Suprapto, Ratih Paramita; Kusumastuty, Inggita; Rizal, Ardian; Adi Nugroho, Dwi (Jurnal Kedokteran Brawijaya, 2024)
Lipopolysaccharide (LPS) is a major component of a gram-negative bacterial wall that is widely used and well-established to induce inflammation in vitro. In addition, the in vitro model using RAW 264.7 cells is the most commonly applied in screening the anti-inflammatory and elucidating the pathophysiology of inflammation-based disease, as well.  However, there is still limited data on the efficacy of different doses of LPS in inducing inflammation in RAW 264.7 cells. This study aimed to evaluate the effect and safety of LPS at various doses in RAW 264.7 cells. RAW 264.7 cells were exposed to LPS at different dose ranges (10ng/mL-10µg/mL) for 24 hours. The nitric oxide (NO) release as inflammatory responses and viability test were evaluated using Griess assay and CCK-8 assays, respectively. The result showed that NO production was increased at different doses of LPS compared to the control although not significant. Whereas, All LPS-treated RAW 264.7 cells tended to increase but not significantly compared to the control groups. This study showed that the LPS treatment effectively induced inflammation in RAW 264.7 cells as shown by NO production and was considerably safe as the viability was comparable between LPS and control group for RAW cells 264.7 at least up to 10µg/mL for 24 hours.